Data monitoring and management system based on ASP.NET and Echarts - Han, Yubao; Ren, Hongwei; Zheng, Yuancheng; Zhou, Haojie (IEEE Advanced Information Management, Communicates, Electronic and Automation Control Conference (IMCEC ...) (Online), 2022)
This paper proposes a data monitoring management system based on ASP.NET and Echarts, the application of B/S development mode, through the use of ASP.NET three-tier architecture and database technology to develop a set of management system with authority management, map module, three-dimensional model module, real-time data monitoring module and historical data monitoring module and other function-s;Through real-time monitoring of environmental factors and other influencing factors, the health status of monitored objects can be evaluated to ensure that their design and use safety and durability meet the expected standards, and provide basis and guidance for the maintenance, repair and management decisions of monitored objects.